The ability to use FLEXPART in simulation of the long-range radioactive materials dispersed from nuclear power plants near Vietnam border - Pham , Kim Long; Nguyen , Hao Quang; Pham , Duy Hien; Do , Xuan Anh; Duong , Duc Thang; Doan , Quang Tuyen (Nuclear Science and Technology, 2016)
FLEXPART is a Lagrangian transport and dispersion model suitable for the simulation of a large range of atmospheric transport processes. FLEXPART has been researched and applied in simulation of the long-range dispersion of radioactive materials. It can be applicable to the problem of radioactive materials released from the nuclear power plants impact on Vietnam. This report presents simulation of radioactive dispersion from the accident assumed Fangchenggang and Changjiang nuclear power plants in China with the FLEXPART, using meteorological data from the National Centers for Environmental Prediction (NCEP). The results of simulations and analyzing showed good applicability of FLEXPART for a long-range radioactive materials dispersion. The preliminary simulation results show that the impact of the radioactive material dispersion in Vietnam varies by the well-known characteristics of the monsoon of our country. Winter is the time when the dominant northeast winds up radioactive dispersion most towards our country, its sphere of influence extends from the Northeast (Quang Ninh) to North Central (Da Nang).